Caracterização da investigação laboratorial de casos suspeitos de dengue no estado de Goiás - Licks, João Guilherme da Silva (2013)
The economic impact of dengue is quite significant, with considerable medical and hospital expenses, vector control and loss of work days. Laboratory confirmation of dengue cases is essential to the identification of the serotype circulating responsible for epidemics. Thus, the dengue surveillance system must be constantly reviewed and updated, contributing for planning and decision making in order to contain the outbreak and prevent damage to the population. This study aimed to characterize the laboratory investigation, taken by the public laboratories of the surveillance system of the state of Goiás, for confirmation of suspected cases of dengue in the health regions. An observational cross-sectional, quantitative study was conducted, analyzing secondary data; and primary data collected with the application of a mixed questionnaire. Additional data were obtained by information from the laboratory test system of the Central Public Health Laboratory of Goiás. The state is divided into 17 health regions, being the Central region the most populous. Two regions are devoid of dengue diagnosis laboratory, two regions are with 2 labs each and the others are with just one each. The Central region was the one that had the highest number of reported cases and deaths due to dengue in the studied period; it’s being also the region with the highest estimated annual and monthly tests performed by laboratory. The study included 73 Coordinators of Epidemiological Nuclei Surveillance from 15 health regions. 100% of the participants in all regions, except the Oeste II and Serra da Mesa, said that they conduct sampling to confirm the diagnosis of dengue. In nine regions most participants informed conduct sampling of every suspected case. In all regions the state laboratory predominated as the reference for the diagnosis of dengue. As the flow of receiving laboratory results, the most frequent was to be transferred to the state and this transfer to the county. Regarding the time of receipt of test results was more frequent the interval of 16 to 30 days for serology. For virus isolation, RT-PCR and immunohistochemistry, most participants ignored this question. The Central Public Health Laboratory of Goiás held, in 2011, 8.723 tests for the diagnosis of dengue, responding the Central region for most of them. As for the serotypes isolated in the state in 2011, the Central region was the only one to present the four circulating serotypes, different from the other regions that showed a single serotype. From these results, it is concluded that the network of laboratories performing diagnosis of dengue in the state is not decentralized in practice, because the majority of participants reported the state laboratory as the reference. We also conclude that it’s not distributed by observing the number of counties, total population, reported cases, deaths and estimated demand for laboratory tests, because of the big difference in these numbers in regions with the same quantitative of laboratories. It is suggested that the distribution of the network should be reconsidered aiming at a better response of the laboratory component of the surveillance.